IMPLEMENTASI RISIKO KECELAKAAN KERJA PADA PROSES PRODUKSI MAKANAN RINGAN DENGAN MENGGUNAKAN METODE HIRARC, HAZOP, DAN FMEA (STUDI KASUS PADA PT. INDOFOOD FORTUNA MAKMUR) - Dian Safhira Firdaus AK; Widodo, Lamto; Adianto (Jurnal Mitra Teknik Industri, 2023)
Occupational accidents are unexpected events, because accidents that cause injuries, disabilities, up to the worst can result in death, or the cessation of the production process. PT. Indofood Fortuna Makmur is a manufacturing company engaged in the production of snacks. In production activities, potential work hazards can be found easily in work areas, in warehouses, production departments and packing departments. During 2021-2022 there were several work accidents that occurred due to worker negligence or potential hazards from the work environment. Based on the results of the HIRARC table for the warehouse, production and packing departments, it can be seen that the most high risks occur in the production department and the results of interviews with employees with the potential for work accidents are more common in the production department. part. One of the risks of work accidents that often occur is workers slipping because of slippery floors. To analyze and carry out implementation in reducing the risk of work accidents, in addition to using the HIRARC method to identify and analyze potential hazard risks, the HAZOP method to classify or classify potential hazards, and the FMEA method are used to determine priority sequences for handling work accidents. The results of this study are in the form of proposed improvements and implementation of the production process of potato chips and tempeh chips at PT. Indofood Fortuna Makmur. The implementation that has been carried out is the use of safety shoes for the production floor area, the use of food tongs in the sorting area, the installation of K3 displays, the socialization of K3. Based on the implementation results that have been carried out, there has been a change in potential risk.